Play, learning and the early childhood curriculum - Wood, Elizabeth (Sage Publications, 2013)
"The third edition of this popular book reflects contemporary research as well as thinking about the role and value of play in learning and development, within and beyond early childhood. The author explores recent developments across international contexts which endorse play, and argues for critical engagement with some aspects of policy discourse in how 'educational play' is constructed. This accessible book also reviews contemporary theoretical The new edition includes coverage of: play in education policies--UK and international perspectives; working with parents; social and cultural diversity; children with special educational needs and disabilities; outdoor play. Each chapter includes case studies provided by practitioners, along with questions and tasks to promote critical engagement and reflection on key issues and debates. This book is for students on childhood studies courses and those on initial teacher education and masters programmes in early childhood and primary education. Experienced practitioners on CPD courses will also find it useful"--Page 4 of cover.